PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF SCHOOLOGY BERBANTUAN SOFTWARE GEOGEBRA MATERI TRANSFORMASI GEOMETRI KELAS XI - Permatasari, Putri Ayu; Dafik, Dafik; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2016)
Abstract. This research is conducted to describe the process of learning media development and to know the product learning media development of mathematic interactive Schoology software Geogebra based on transformation geometry at class XI SMKN 2 Jember. This research is research of development based on development model 4D that describe by Thiagarajan wich consist of 4 stages, namely define, design, develop and disseminate. Subject of this research is students of class XI at SMKN 2 Jember at Multi Media with 1 thep students number are 32 students. Data collection in this research used validation sheets model from 3 validators, teachers interview, user quetionair and students score test. The result was analysed in descriptive form the result of research, the result of the media’s validity level is 93% or in other words the prevalence level is in the “High” category, the practical level is seen from students activity quetionnaire researching 84,2% or can be categorized as “Good” and the effectiveness level of 81,25% is in the “Practical” criterion, so it can be said that developed learning media worthy to be tested. Keywords : Geogebra, Learning Media, 4D Thiagaran Models, Schoology.